Ensino Remoto: Desafios e possibilidades do fazer docente em tempos de pandemia na Educação Infantil e nos anos iniciais do Ensino Fundamental - Oliveira, Fernanda da Silva Leite (Universidade Federal do Tocantins, 2023)
This study’s theme is the teaching work in Remote Teaching, through which we seek to understand the challenges and possibilities of working this way for teachers of Kindergarten and the early years of Elementary School, in order to identify the impacts on their practices and the way they are dealing with the restructuring of teaching work in the current context. As specific objectives, we sought to: i) describe the challenges faced by teachers; ii) identify the limits and possibilities of the work carried out in Remote Education; iii) reflect on the precariousness and intensification of work and its effects on the development of teachers' practices; and iv) explain the demands that emerged in the training and preparation of these professionals to work with children in the pandemic context. This research has a qualitative approach, made through field research, in which we use semi-structured interviews as an instrument for data collection. The interviews were conducted with five teachers: four who live in Campos Belos-GO and work in schools in the municipal education network, and one who lives in Arraias-TO, a teacher in a teaching cooperative. we based our reflections and analyzis on the discussions proposed by the research group “Alfabetização em Rede” (2020) and on studies by Gonçalves and Guimarães (2020), Macedo (2020), Freire (1996; 1997) and others. This study allowed us to understand that Remote Teaching represents a great challenge for the teachers interviewed, mainly because they did not receive training and did not have access to resources that could contribute to the better development of their practices. Furthermore, it was clear in the teacher’s testimonies that work remotely enabled the construction of a new learning as they had to adapt their practices to the context, but also generated an overwhelming amount of work for these professionals and, at times, the occurrence of negative feelings, such as insecurity, concern, stress, frustration and anguish, arising from the context and aspects that permeate practices in Remote Education, such as the precariousness of working conditions that were intensified during the Covid-19 pandemic.